Two Parameters of The Sewer Base - Hakimjonovich , Muradov Rakhimjon; Islamjon, Olimjonov (American Journal of Botany and Bioengineering, 2026)
Considering that the designs of existing seed machine coulters are not suitable for sowing wheat seeds in between the cotton rows, a new streamlined coulter design has been proposed. The article presents the results of studies to substantiate the parameters of the coulter while it’s working in between the cotton rows, taking into account its interaction with the soil. Dependencies are obtained to determine the entry angle of the coulter’s knife into the soil, the curvature radius of the knife’s front, the sharpening angle of the knife’s front, and the resistance force of the coulter’s knife.